1995
DOI: 10.1159/000246537
|View full text |Cite
|
Sign up to set email alerts
|

Reticular Erythematous Mucinosis Associated with Human Immunodeficiency Virus Infection

Abstract: We report the case of a 56-year-old woman with reticular erythematous mucinosis (REM). During her workup infection with the human immunodeficiency virus (HIV) was detected. She developed a cerebral toxoplasmosis, salmonella sp. bacteremia and oral ulcerations with the presence of type I herpes simplex virus and cytomegalovirus. The relation of REM with the deposition of mucin in AIDS patients’ bone marrow and HIV infection is discussed. To our knowledge, this is the first report where REM is associated with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Cytomegalovirus (CMV) identified in perianal ulcers is often in association with other infectious organisms. It may not be pathogenetic, but should prompt a search for CMV infection elsewhere in the body [24]. Chancroid and granuloma inguinale can present perianally but are rare in developed countries, and are not discussed further here [25].…”
Section: Sexually Transmitted Diseasesmentioning
confidence: 99%
“…Cytomegalovirus (CMV) identified in perianal ulcers is often in association with other infectious organisms. It may not be pathogenetic, but should prompt a search for CMV infection elsewhere in the body [24]. Chancroid and granuloma inguinale can present perianally but are rare in developed countries, and are not discussed further here [25].…”
Section: Sexually Transmitted Diseasesmentioning
confidence: 99%
“…Generally, CMV skin lesions are rare and its presence may signify the development of systemic infection with poor outcome 5 . CMV infection may coexist with other infections such as HSV and varicella zoster virus infection 6 . It has been reported that the presence of persistent anogenital ulcers in HIV infected patients may be a marker of CMV in the lesions 1,6 .…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, it is difficult to determine whether the ulcerative lesion was due to CMV or HSV, as CMV may contribute to the maintenance of an existing ulcerative lesion. Histology is reported to be the most sensitive method to detect CMV 6 . Other detection methods include cell culture, immunohistochemistry using indirect immunofluorescence, polymerase chain reaction to detect CMV DNA and serology.…”
Section: Discussionmentioning
confidence: 99%
“…The association between mucin deposit and HIV infection in several cutaneous and systemic diseases has been described: papular mucinosis [10, 11, 12], pityriasis rubra pilaris [13], reticular erythematous mucinosis [14], breast carcinoma [15]and ocular calcification [16], among others. It is a well-known phenomenon that in 29% of patients with AIDS, focal or generalized extracellular deposits of mucin in bone marrow have been detected [17].…”
Section: Discussionmentioning
confidence: 99%